2022
DOI: 10.15625/2525-2518/16634
|View full text |Cite
|
Sign up to set email alerts
|

Genus mallotus (euphorbiaceae): a review on traditional medicinal use, phytochemistry and biological activities

Abstract: Ethnopharmacological relevance: The genus Mallotus (Euphorbiaceae family) includes 124 accepted names and distributes in tropical and sub-tropical regions. Some Mallotus species are used in traditional medicines for the treatment of chronic hepatitis, enteritis stomach, disorders, cholelithiasis, anti-cancer,  gastric, and duodenal ulcers. Aim of the study: According to the Scifinder database, this is the first review study that focuses on the phytochemistry and pharmacology of Mallotus genus (17 Mallotu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…Taken together, our results show that the zebrafish embryotoxicity test reveals potential toxic or developmental effects caused by extracts from traditional medicinal plants ( Table 4 ). The traditional use of the different medicinal plants investigated here range from anti-inflammatory, stomachache, and duodenum ulcers (KT14), anti-tumor (KT09, KT11, KT14, KT20), antioxidant, antimicrobial to antiviral [ 72 , 80 , 81 ]. A literature review of their chemical composition revealed compounds of particular interest, such as quercetin, ursolic acid, berberine and palmatine [ 72 , 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, our results show that the zebrafish embryotoxicity test reveals potential toxic or developmental effects caused by extracts from traditional medicinal plants ( Table 4 ). The traditional use of the different medicinal plants investigated here range from anti-inflammatory, stomachache, and duodenum ulcers (KT14), anti-tumor (KT09, KT11, KT14, KT20), antioxidant, antimicrobial to antiviral [ 72 , 80 , 81 ]. A literature review of their chemical composition revealed compounds of particular interest, such as quercetin, ursolic acid, berberine and palmatine [ 72 , 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compounds isolated from M. oppositifolius showed potent antioxidant, antibacterial and antimalarial activities. The root extract of M. apelta and compounds isolated from M. japonicus showed significant antiviral activity (2) . M. roxburghianus has been reported to contain phenols, alkaloids, saponins, terpenes, tannins, triterpenoids, steroids, reducing sugars, coumarin, berginin, gallic acid, gentisic acid, gums, and a variety of other natural substances, particularly flavonoids like chrysin, hesperidin, naringenin, quercetin, and rutin.…”
Section: Introductionmentioning
confidence: 99%